Saruq al-Hadid: a persistent temporary place in late prehistoric Arabia. Issue 1 (1st January 2019) - Weeks, L.; Cable, C.M.; Franke, K.A.; Karacic, S.; Newton, C.; Roberts, J.; Stepanov, I.; McRae, I.K.; Moore, M.W.; David-Cuny, H.; Al Aali, Y.Y.; Boraik, M.; et al.
ABSTRACT: In this paper, the authors use the site of Saruq al-Hadid – a 'persistent temporary place' located in the mobile dune fields of the north eastern edge of the Rub' al-Khali desert – as a lens to focus discussion on the variable nature of temporary sites and mobile adaptations within the archaeology of southeastern Arabia, the relationships between temporary sites and permanent settlements, and the evidence for collective events and gatherings from later prehistory into the Islamic period. They discuss evolving arguments regarding sedentary and mobile sites and groups in Arabia from the Neolithic period to the Iron Age, and summarize the material record of human activity at Saruq al-Hadid. This research emphasizes the site's changing significance as a temporary place and its emergence, in the early Iron Age, as a locus for periodic interaction between multiple community groups.